CD4+CD28null T cells are expanded in moderately active systemic lupus erythematosus and secrete pro-inflammatory interferon gamma, depending on the Disease Activity Index. (June 2020) - Kosmaczewska, Agata; Ciszak, Lidia; Stosio, Malgorzata; Szteblich, Aleksandra; Madej, Marta; Frydecka, Irena; Wiland, Piotr; Szmyrka, Magdalena
Background: Pathogenic CD4 + CD28 null cells are characterized by inflammatory cytokine synthesis and tropism to the inflamed tissues. Recent studies showed the involvement of CD28 null T cells in a severe clinical outcome of lupus. However, their role in moderately active disease is still unresolved. Methods: We examined the levels of circulating CD4 + CD28 null cells and CD8 + CD28 null suppressor T cells. We also compared the CD4 + CD28 null and CD4 + CD28 + T-cell functional properties, including the expression of interferon gamma (IFN-γ) and Ki67 among systemic lupus erythematosus (SLE) patients ( n  = 20) and healthy controls ( n  = 20). All the patients were under immunosuppressive treatment and exhibited moderate SLE activity (median SLE Disease Activity Index (SLEDAI) = 6). Results: In patients, we found elevated CD4 + CD28 null and unchanged levels of suppressor CD8 + CD28 null T cells. There was no difference between patients and controls in IFN-γ and Ki67-expressing CD4 +, CD4 + CD28 +, and CD4 + CD28 null T cells, except for higher IFN-γ levels in CD4 + CD28 + T cells in SLE. In each studied group, we observed a higher preponderance of IFN-γ- and Ki67-expressing cells among CD4 + CD28 null T cells and lower levels of IFN-γ in CD4 + CD28 null T cells compared to the CD28+ subset. Similarly, Ki67 intensity was decreased in healthy CD4 + CD28 null cells, whereas in patients, comparably high expression was observed in both subsets. IFN-γ intensity in CD4 + CD28 null T cells correlated with SLEDAI. Conclusion: SLE with a moderately active clinical course is characterized by peripheral blood expansion of CD4 + CD28 null T cells and a normal abundance of suppressor CD8 + CD28 null T cells. The demonstration that these pathogenic CD4 + T cells, despite the lack of CD28, maintain the ability to produce pro-inflammatory IFN-γ positively correlated with disease activity as well as relatively high proliferative capacity may suggest their potentially predictive role in SLE flares.